Phase Angle following Intradialytic Neuromuscular Electrical Stimulation and Oral Protein Supplementation in Patients undergoing Chronic Hemodialysis - Jungho Shin; Jae Hyeon Park; Jae Yoon Park; Ran-hui Cha (Annals of Geriatric Medicine and Research)
Background Sarcopenia is a prevalent condition in patients undergoing chronic hemodialysis. Therefore, a convenient and reliable method of monitoring muscle health is required. This study identified the utility of the phase angle (PhA) to estimate muscle health, and evaluated its changes following intradialytic neuromuscular electrical stimulation (NMES) and oral nutritional supplement interventions in patients undergoing chronic hemodialysis. Methods This post-hoc analysis was conducted using data obtained from a 12-week multicenter randomized trial that examined the effects of NMES and protein supplementation. The participants were divided into four groups according to intradialytic NMES and protein supplementation. The PhA, muscle mass, muscle strength, and physical performance were measured every 4 weeks. Results Overall, 59 participants completed the study. PhA values were linearly associated with muscle mass and muscle strength. Additionally, high PhA levels indicated fast gait speed and shortened timed up-and-go test (TUG) results. We further evaluated the association between the PhA slope and muscle health-related parameters. In participants with the PhA slope <0° over 12 weeks, TUG results worsened over time, relative to those with a slope ≥0° over 12 weeks, independent of age, sex, diabetes, and body mass index. NMES did not improve the PhA values over time; however, protein supplementation tended to increase the PhA values. Conclusion PhA is a reliable marker for estimating and monitoring muscle health in patients undergoing chronic hemodialysis, and a strong association exists between PhA and TUG results.